Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2020)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated corn in western Kansas. In 2019, N applied alone increased yields by 71 bu/a, whereas P applied alone increased yields 10 bu/a. Nitrogen and P applied together increased yields up to 131 bu/a, which is 10 bu/a less than the 10-year average of 141 bu/a. Application of 120 lb N/a (with highest P rate) produced 97% of maximum yield in 2019, which is slightly greater than the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields 4 bu/a. Average grain N content reached a maximum of 0.6 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu). At the highest N and P rate, apparent fertilizer nitrogen recovery in the grain (AFNRg) was 41% and apparent fertilizer phosphorus recovery in the grain (AFPRg) was 60%.
Keywords: long-term nitrogen; nitrogen; phosphorus; irrigated corn; fertilizer